The Effect Of Motivation And Reward System On Employee Performance With Commitment As A Mediation Variable - Aru Setiawan, Muhammad; Ribhan; Nova Mardiana (International Journal of Science, Technology & Management, 2022)
Employee performance is inseparable from efficiency and effectiveness. Efficiency emphasizes work results, while effectiveness relates to the process of achieving goals related to human work or increasing human labor, life and cultural renewal, mental attitude of glorifying work and expanding efforts to improve the quality of people’s lives. In other words, the process of increasing work productivity can be done through motivation, education, work discipline, skills, technology, work ethic attitudes, income levels, work environment and climate, management, achievement opportunities and production facilities as well as social security, work ethic, work loyalty. , job satisfaction, leadership, organizational structure and supervision. The research design is generally divided into 3 (three) forms, namely explorative research, descriptive research and explanatory research. Explorative research is a type of research that seeks to find new ideas or relationships. While descriptive research is research that aims to describe the properties or characteristics of a particular phenomenon. Finally, explanatory research is research that aims to analyze the relationships between one variable and another or how one variable affects other variables. Based on the discussion that has been carried out, the results of this study are as follows: 1) Motivation (X1) has a positive and significant effect on performance (Y) and the hypothesis is accepted. 2) Reward (X2) has a positive and significant effect on performance (Y) and the hypothesis is accepted. 3) Reward moderated by the commitment variable (X2X3) has a positive and significant effect on performance (Y) and the hypothesis is accepted.